Mineral profile of imported pet food in Costa Rica - Cedeño-López, André; WingChing-Jones, Rodolfo (Agronomía Mesoamericana, 2022)
Introduction. The mineral content in pet food is not always displayed on the label. It is important to know this information in order to assess the nutritional contribution of the food. Objective. To determine the content of Ca, P, K, Na, Mg, S, Cu, I, Fe, Mn, and Zn in 34 imported foods for dogs, cats, rabbits, hamsters, ornamental fish, and turtles, and to compare the results with the recommendations found in the literature. Materials and methods. During the months of August and December of 2018, ten samples were collected of dog and cat food, five for ornamental fishes, four for turtles, three for hamsters, and two for rabbits. These were acquired directly at different points of sale in the Greater Metropolitan Area, San Jose, Costa Rica. The samples were analyzed at the Animal Nutrition Research Center of the Universidad de Costa Rica. The minerals Ca, P, K, Mg, S, Cu, I, Fe, Mn, and Zn were quantified based on the methodology recommended by the Association of Official Analytical Chemists. The average content per feed group according to the animal species, standard deviation, maximum and minimum values were calculated compared with the nutritional recommendations for minerals found in the literature. Results. The foods studied met, on average, the mineral requirements for pets. Imbalances in Ca, P, and Mg content in the turtle foods, high iodine contents in dog foods, and unbalanced mineral relations were observed. Conclusions. A database was generated with average values and their dispersion in eleven minerals in 34 samples of commercial foods for seven companion animals in Costa Rica. Little information was available regarding the recommended upper limits and requirements in species such as hamsters, ornamental fish or turtles.